The Anti-Inflammatory Effect of KS23, A Novel Peptide Derived From Globular Adiponectin, on Endotoxin-Induced Uveitis in Rats - Xin Shi; Xin Shi; Xin Shi; Xin Shi; Xin Shi; Shaopin Zhu; Shaopin Zhu; Shaopin Zhu; Shaopin Zhu; Shaopin Zhu; Huiyi Jin; Huiyi Jin; et al. (Frontiers Media S.A., 2021)
Purpose: Adiponectin has been shown to exert potent anti-inflammatory activities in a range of systemic inflammatory diseases. This study aimed to investigate the potential therapeutic effects of KS23, a globular adiponectin-derived peptide, on endotoxin-induced uveitis (EIU) in rats and lipopolysaccharide (LPS)-stimulated mouse macrophage-like RAW 264.7 cells.Methods: EIU was induced in Lewis rats by subcutaneous injection of LPS into a single footpad. KS23 or phosphate-buffered saline (PBS) was administered immediately after LPS induction via intravitreal injection. Twenty-four hours later, clinical and histopathological scores were evaluated, and the aqueous humor (AqH) was collected to determine the infiltrating cells, protein concentration, and levels of inflammatory cytokines. In vitro, cultured RAW 264.7 cells were stimulated with LPS in the presence or absence of KS23, inflammatory cytokine levels in the supernatant, nuclear translocation of nuclear factor kappa B (NF-κB) subunit p65, and the expression of NF-kB signaling pathway components were analyzed.Results: KS23 treatment significantly ameliorated the clinical and histopathological scores of EIU rats and reduced the levels of infiltration cells, protein, tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) in the aqueous humor. Consistently, KS23 decreased the expression of TNF-α and IL-6 in the supernatant of LPS-stimulated RAW 264.7 cells and inhibited the LPS-induced nuclear translocation of NF-κB p65 and the phosphorylation of IKKα/β/IκBα/NF-κB.Conclusion: The in vivo and in vitro results demonstrated the anti-inflammatory effects of the peptide KS23 and suggested that KS23 is a compelling, novel therapeutic candidate for the treatment of ocular inflammation.